PENGARUH LITERASI KEUANGAN TERHADAP PERILAKU KONSUMTIF MAHASISWA JURUSAN PIPS FKIP UNIVERSITAS RIAU - Charles, Charles; Srikartikowati, Srikartikowati; Riadi, R.M (Jurnal Online Mahasiswa (JOM) Bidang Keguruan dan Ilmu Pendidikan, 2019)
Abstract: This research aims to determine the effect of financial literacy on consumptive behavior of college students. This research was conducted in the Department of Social Science Education University of Riau. The research using quantitative methods. The population in this research is student of Depertemen of Social Science Education University of Riau consisted of three Study Program (Economic Education, Civic Education and History Education) the level of 2015, 2016 and 2017 total 741 students. Sample was taken by stratified random sampling technique. Data was collected using quisioneries, then was analized by simple regression method. The research showed that there is an effect of financial literacy on consumer behaviour at students in Department Social Science Education University of Riau is 0.271 or 27.1%. 72.9% while the rest is affected by other factors that do not examined in this study.Key Words: Financial Literacy, Consumer Behavior